Respuesta :
Explanation :-
- let one number be x.
- And the other will be ( x+1)
[tex]\qquad[/tex] According to the question :-
[tex]\qquad \pmb{\sf\longrightarrow (x+1)+x = 63}[/tex]
[tex]\qquad \pmb{\sf\longrightarrow x+1+x=63}[/tex]
[tex]\qquad \pmb{\sf\longrightarrow 2x+1=63}[/tex]
[tex]\qquad \pmb{\sf\longrightarrow 2x=63-1}[/tex]
[tex]\qquad \pmb{\sf\longrightarrow x=\cancel{\dfrac{62}{2}}}[/tex]
[tex]\qquad \longrightarrow {\pink{\underline{\underline{\pmb{\sf{ x= 31}}}}}}[/tex]
Verification:-
[tex]\qquad \pmb{\sf\longrightarrow (x+1)+x=63}[/tex]
[tex]\qquad \pmb{\sf\longrightarrow 32+31=63}[/tex]
[tex]\qquad \pmb{\sf\longrightarrow 63=63}[/tex]
Therefore–
- The two consecutive natural numbers whose sum is 63 will be x=31 and x+1=31+1=32
▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬